Side effects of fiscal rules: a case of Polish local self‑government - Banaszewska, Monika (Economics and Business Review, 2018)
The trend towards decentralization of government activities has promptedan increased interest in sub-national fiscal rules. The paper investigates an ex ante adaptationto the modified subnational fiscal framework. Using a panel of 2,479 Polishmunicipalities in the years 2011-2013 the aim is to verify the existence of the side effectof the new debt repayment rule. The empirical results show that local governmentunits for which the new rule would have been more demanding than the former generatedhigher revenues per capita from asset sales.